Comparative Study of Coaxial Main Rotor Aerodynamics in the Hover with the Usage of Two Methods of Computational Fluid Dynamics - Konstantinov,Sergey Gennadievich (2021)
ABSTRACT The paper is focused on numerical modeling of the aerodynamic characteristics of a full-scale coaxial main rotor in hover. The simulation was performed using two approaches of computational fluid dynamics (CFD): the original free wake model (FWM) developed by the authors and the unsteady Reynolds-averaged Navier–Stokes (URANS) equations method based on the Ansys Fluent software. The structure of the rotor vortex wake, flow images, vorticity and induced velocity fields, total and distributed aerodynamic characteristics of the rotor, including the rotor performance and figure of merit diagrams, have been analyzed. A comparison between FWM/URANS based calculations and calculated/experimental data by other authors has been performed. A satisfactory match of these data confirms reliability of used methods when modeling the aerodynamic characteristics of coaxial rotors. The FMW demonstrates a significant advantage in speed and resources intensity when calculating the total aerodynamic characteristics of a coaxial rotor. The URANS method makes it possible to model with significant accuracy the effects associated with the blade vortex interactions and pressure distribution over the blade surface. Finally, conclusions about most effectiveness of joint application of considered methods in solving complex problems of coaxial rotor aerodynamics has been made.